Genomic signatures of inbreeding in a critically endangered parrot, the kākāpō. Issue 11 (31st August 2021) - Foster, Yasmin; Dutoit, Ludovic; Grosser, Stefanie; Dussex, Nicolas; Foster, Brodie J; Dodds, Ken G; Brauning, Rudiger; Van Stijn, Tracey; Robertson, Fiona; McEwan, John C; Jacobs, Jeanne M E; Robertson, Bruce C
Abstract: Events of inbreeding are inevitable in critically endangered species. Reduced population sizes and unique life-history traits can increase the severity of inbreeding, leading to declines in fitness and increased risk of extinction. Here, we investigate levels of inbreeding in a critically endangered flightless parrot, the kākāpō ( Strigops habroptilus ), wherein a highly inbred island population and one individual from the mainland of New Zealand founded the entire extant population. Genotyping-by-sequencing (GBS), and a genotype calling approach using a chromosome-level genome assembly, identified a filtered set of 12, 241 single-nucleotide polymorphisms (SNPs) among 161 kākāpō, which together encompass the total genetic potential of the extant population. Multiple molecular-based estimates of inbreeding were compared, including genome-wide estimates of heterozygosity (FH ), the diagonal elements of a genomic-relatedness matrix (FGRM ), and runs of homozygosity (RoH, FRoH ). In addition, we compared levels of inbreeding in chicks from a recent breeding season to examine if inbreeding is associated with offspring survival. The density of SNPs generated with GBS was sufficient to identify chromosomes that were largely homozygous with RoH distributed in similar patterns to other inbred species. Measures of inbreeding were largely correlated and differed significantly between descendants of the two founding populations. However, neither inbreeding nor ancestry was found to be associated with reduced survivorship in chicks, owing to unexpected mortality in chicks exhibiting low levels of inbreeding. Our study highlights important considerations for estimating inbreeding in critically endangered species, such as the impacts of small population sizes and admixture between diverse lineages.